2015
DOI: 10.1111/acem.12631
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Serial Ultrasound Clinical Diagnostic Pathway in Suspected Appendicitis and Related Computed Tomography Use

Abstract: Objectives: The primary objective was to determine the diagnostic accuracy of a serial ultrasound (US) clinical diagnostic pathway to detect appendicitis in children presenting to the emergency department (ED). The secondary objective was to examine the diagnostic performance of the initial and interval US and to compare the accuracy of the pathway to that of the initial US.Methods: This was a prospective cohort study of 294 previously healthy children 4 to 17 years old with suspected appendicitis and baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 58 publications
1
33
1
3
Order By: Relevance
“…These findings in present study were comparable with findings of Schuh S et al and many other studies. 18 However, some of the studies have integrated other parameters like CRP with USG and increases the sensitivity and specificity which is contrary to the findings in present study. 19 In present study, the utility of ultrasound has been advocated as an adjunct to improve diagnosis in equivocal cases and determines further who needs further imaging with superior modality.…”
Section: Discussioncontrasting
confidence: 95%
“…These findings in present study were comparable with findings of Schuh S et al and many other studies. 18 However, some of the studies have integrated other parameters like CRP with USG and increases the sensitivity and specificity which is contrary to the findings in present study. 19 In present study, the utility of ultrasound has been advocated as an adjunct to improve diagnosis in equivocal cases and determines further who needs further imaging with superior modality.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar to our study, Schuh et al reported a suboptimal accuracy rate (60%) of screening with ultrasound scanning for appendicitis (21). Recent study showed that the serial US has a higher diagnostic accuracy than initial US (22). First reason for our lower specificity and accuracy may be due to using only initial US in ED.…”
Section: Discussionsupporting
confidence: 80%
“…This diagnostic modality does not expose the patient to ionizing radiation and is currently recommended by the American College of Radiology following an equivocal US in pregnant women (5). A second US examination could also be considered as a follow-up imaging technique (8,11). It is expected that the second US may have a better diagnostic performance compared with the initial US because the progression of the inflammatory process in the appendix would make it easier to be detected.…”
mentioning
confidence: 99%